How sectoral technical progress and factor substitution shaped Japan's structural transformation? - Ana-Simona Manu (European Central Bank (ECB), 2022)
The paper quantitatively assesses the importance of supply-side drivers in the transition of the Japanese economy from low-skilled to high-skilled sectors and its implication for growth, labor demand and labor income shares. A sectoral supply-side system, estimated over the 1980-2012 period, reveals different rates of technical progress across production factors and sectors, but also heterogeneity in the sectoral elasticity of substitution between capital and labor. The fact that capital and labor are easily substitutable in low-skilled services but not in high-skilled services, coupled with the dominant role of capital-augmenting technical change in services is a key factor behind the relocation of labor towards high-skilled services, as well as behind the declining trend in the labor income share in low-skilled services.
Keywords: O47; O33; J23; 330; CES production function; biased technical change; labor demand; labor income share